Forensic entomology: the influence of the burning of a body on insect succession and calculation of the postmortem interval - Kolver, Jacobus Hendrik (University of the Free State, 2009)
Forensic entomology is the application of the study of insects and other arthropods which are associated with legal issues and certain suspected criminal events. Successional studies have been successfully applied in criminal cases to determine the postmortem interval (PMI). This research was done to establish the influence of burning on a body’s decomposition, insect succession and calculation of the PMI. Field trials were conducted during different seasons of successive years on the campus of the University of the Free State, Bloemfontein, South Africa. The experimental site where the field experiments were conducted, consists of 24 hectares of open grassveld with a few scattered trees. Four pig (Sus scrofa) carcasses were used during each trial, one carcass as control and three carcasses burnt with different volumes of LRP petrol to a CGS level 2 or 3 burn injury with varying degrees of charring. The carcasses were sampled daily for arthropod activity, carcass mass, decompositional stage and microclimate. The control and SB (slightly burnt) carcasses decomposed at a similar rate during the warmer seasons. During the colder seasons, the SB carcass decomposed faster than the control carcass. The slowest decomposition occurred at the MB (medium burnt) and HB (heavily burnt) carcasses. Burning had an effect on the colonisation of Chrysomya chloropyga, Chrysomya marginalis and Chrysomya albiceps. Oviposition occurred simultaneously at all carcasses (autumn, spring & during heavy rainfall in summer ), at the burnt carcasses one day prior to the control carcass (spring & summer) and at the burnt carcasses three to five days prior to the control carcass (autumn & winter). An exception occurred during a single trial when oviposition occurred at the burnt carcasses five days after oviposition at the control carcass (winter). During the warmer seasons oviposition time was shorter, resulting in maggots of similar age at all of the carcasses. During the colder seasons oviposition time was extended, resulting in maggots of different ages and instars on the same carcass and between carcasses. During all trials, except for the summer trail with heavy prolonged rainfall, only the control carcasses reached the Dry/Remains Stage. The burnt carcasses only reached the Advanced Decomposition Stage during the same timeframe. Calliphoridae were the dominant Diptera during all trials. Dominant Diptera species, in numerical order, were Chrysomya marginalis, Chrysomya albiceps and Chrysomya chloropyga. Muscidae adults were recorded during all trials, but no maggots were observed or collected. Coleoptera were dominated by Dermestes maculatus (adults and larvae) and Necrobia rufipes (adults). Coleoptera dominance increased with the level of burning. Differences in arthropod succession between the carcasses occurred due to the effect of burning on the time of oviposition. The PMI calculated for a burnt body would be one to five days shorter than the PMI for an unburnt body, depending on the extent of bloating of the burnt body, the season and ambient temperature. During warmer months the PMI of a burnt body and an unburnt body would essentially be the same due to simultaneous oviposition. Laboratory trials revealed that feeding on burnt media caused C. chloropyga maggots to reach pupation one day faster than the control. No significant difference was found between the treatments for the development time from pupation until adult eclosion. No significant difference was found between the treatments for the mean total development time for C. chloropyga. A 10.6% higher survival until adulthood was found on the burnt media than the control. Morphometrics revealed a higher pupal mass for the control than the burnt media. No signifant difference was found for the adult dry mass and wing length for the control and the burnt media.
Thesis (Ph.D. (Zoology and Entomology))--University of the Free State, 2009
Keywords: Forensic entomology; Postmortem changes; Indicators (Biology); Arthropoda -- Life cycles; Diptera; Beetles; Blowflies; Coleoptera; Calliphoridae; PMI; Postmortem interval; Burning; Arthropod succession; Oviposition